Novel selective TOPK inhibitor SKLB-C05 inhibits colorectal carcinoma growth and metastasis. (31st March 2019) - Gao, Tiantao; Hu, Quanfang; Hu, Xi; Lei, Qian; Feng, Zhanzhan; Yu, Xi; Peng, Cuiting; Song, Xuejiao; He, Hualong; Xu, Ying; Zuo, Weiqiong; Zeng, Jun; et al.
Abstract: The mitogen-activated protein kinase (MAPK) signaling pathway member T-LAK cell–originated protein kinase/PDZ-binding kinase (TOPK/PBK) is closely involved in tumorigenesis and progression. Its overexpression in colorectal carcinoma (CRC) exacerbates tumor malignancy, promotes metastasis and results in dismal prognosis. Therefore, targeting TOPK is a promising approach for CRC therapy. Here, we report the development of a TOPK selective inhibitor SKLB-C05, with subnanomolar inhibitory potency. In vitro, SKLB-C05 exhibited excellent cytotoxicity and anti-migration and invasion activity on TOPK high-expressing CRC cells and induced cell apoptosis. These activities could attribute to its inhibition of TOPK downstream signaling including extracellular signal-regulated kinase 1/2 (ERK1/2), p38, and c-Jun N-terminal kinase 1, 2, and 3 (JNK1/2/3), as well as downregulation of FAK/Src- MMP signaling. Furthermore, SKLB-C05 disrupted cell mitosis and blocked CRC cell cycle. In vivo, oral administration of SKLB-C05 at concentrations of 20 and 10 mg kg −1 ·day −1 dramatically attenuated CRC tumor xenograft growth and completely suppressed hepatic metastasis of HCT116 cells, respectively. Thus, these findings suggest that SKLB-C05 is a specific TOPK inhibitor with potent anti-CRC oncogenic activity in vitro and in vivo . Highlights: SKLB-C05 selectively inhibit TOPK kinase with subnanomolar potency. SKLB-C05 exhibit anti-proliferative activity only on TOPK-positive CRC cells. SKLB-C05 markedly inhibit tumor growth and hepatic metastasis of CRC. SKLB-C05 down-regulate TOPK mediated signaling pathway. FAK/Src-MMPs signaling promote CRC metastasis and SKLB-C05 inhibit the pathway.